2016
DOI: 10.1016/j.cub.2016.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Endolysosomes Are the Principal Intracellular Sites of Acid Hydrolase Activity

Abstract: SummaryThe endocytic delivery of macromolecules from the mammalian cell surface for degradation by lysosomal acid hydrolases requires traffic through early endosomes to late endosomes followed by transient (kissing) or complete fusions between late endosomes and lysosomes. Transient or complete fusion results in the formation of endolysosomes, which are hybrid organelles from which lysosomes are re-formed. We have used synthetic membrane-permeable cathepsin substrates, which liberate fluorescent reporters upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
244
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(277 citation statements)
references
References 49 publications
(61 reference statements)
13
244
0
Order By: Relevance
“…Recent work has shown that after ended hydrolytic digestion, endolysosomes form into small non-acidic storage lysosomes containing inactive lysosomal hydrolases [13]. These storage lysosomes can then fuse to LEs and existing endolysosomes to recycle their content of lysosomal constituents and regenerate lysosomal compartments (see model in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that after ended hydrolytic digestion, endolysosomes form into small non-acidic storage lysosomes containing inactive lysosomal hydrolases [13]. These storage lysosomes can then fuse to LEs and existing endolysosomes to recycle their content of lysosomal constituents and regenerate lysosomal compartments (see model in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These processes generate hybrid endo- and autolysosomal compartments, in which degradation catalyzed by lysosomal enzymes takes place. Following the completion of digestion, endolysosomes condense to reform small lysosomes that function as storage organelles for resident hydrolases [13]. …”
Section: Introductionmentioning
confidence: 99%
“…We thus sought a way to follow ESCRT dynamics during both the onset and resolution of endolysosomal injury. Briefly exposing cells to lysosomotropic rupturing agents induces transient membrane disruption (9, 11, 27, 36) and accordingly, cells treated with LLOME for less than a minute acquired ESCRT puncta shortly after adding drug but not at later times (fig. S20).…”
Section: Escrts Are Transiently Recruited Following Acute Membrane Damentioning
confidence: 99%
“…GPN (glycyl-L-phenylalanine 2-naphthylamide) is an alternative rupturing agent that accumulates in endolysosomes like LLOME (11, 27). However, GPN is processed into metabolites thought to promote osmotic rupture (27, 37) potentially similar to damage caused by materials that normally transit the endolysosomal network.…”
Section: Escrts Are Transiently Recruited Following Acute Membrane Damentioning
confidence: 99%
See 1 more Smart Citation